Enhanced Calvarial Bone Healing in CD11c-TLR4−/− and MyD88−/− Mice. Issue 4 (April 2017) - Wang, Dan; Taylor, Gwen M.; Gilbert, James R.; Losee, Joseph E.; Sodhi, Chhinder P.; Hackam, David J.; Billiar, Timothy R.; Cooper, Gregory M.
Abstract : Background: Inflammation is integral to the injury response. The inflammatory response is essential to the host defense against infection and also to tissue regeneration and repair. Toll-like receptors (TLRs) are critical activators of the innate immune response and present attractive therapeutic targets for inflammation-modulated tissue regeneration. The authors' previous study showed that depletion of TLR4 resulted in accelerated skull bone healing concurrent with increased expression of osteoclastogenic genes. As such, in the present study, the authors used various knockout mouse models for TLR4 and its associated signaling mediators as tools to further understand the role of Toll-like receptor–mediated inflammation in calvarial bone healing. Methods: Calvarial defects (1.8-mm diameter) were created in wild-type, TLR4 knockout (TLR4 −/− ), TLR2 −/−, MyD88 −/−, TRIF −/−, TLR4 knockout in myeloid cell (Lyz-TLR4 −/− ), and TLR4 knockout in dendritic-lineage cell (CD11c-TLR4 −/− ) mice. Bone healing was examined using micro–computed tomographic, histologic, and histomorphometric analyses. Results: Micro–computed tomographic and histomorphometric analyses revealed that TLR4-deficient mice (TLR4 −/−, Lyz-TLR4 −/−, and CD11c-TLR4 −/− ) exhibited a faster intramembraneous healing response at postoperative day 7, whereas MyD88 −/− and CD11c-TLR4 −/− mice showed enhanced bone healing at day 28. Conclusions: The authors' data suggest a detrimental role for TLR4 in CD11c + cells, mediated by Myd88 signaling, during calvarial bone healing. The authors have demonstrated that Toll-like receptor signaling components affect calvarial bone healing, establishing a link between the skeletal and immune systems during craniofacial bone healing. Toll-like receptor signaling components might be used to initiate enhanced healing in bone defects to improve clinical outcomes. Abstract : Supplemental Digital Content is available in the text.